2016
DOI: 10.1016/j.rmed.2016.09.018
|View full text |Cite|
|
Sign up to set email alerts
|

Efficacy and safety comparison: Fluticasone furoate and fluticasone propionate, after step down from fluticasone furoate/vilanterol in Japanese patients with well-controlled asthma, a randomized trial

Abstract: For patients with well-controlled asthma on mid dose ICS/LABA (equivalent to FP/SAL 250/50 μg BD), control can be maintained when they are stepped across to FF/VI 100/25 μg OD. FF 100 μg OD is an effective step-down therapy from FF/VI 100/25 μg OD with similar efficacy to FP 100 μg BD and FP 250 μg BD.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 20 publications
0
8
0
Order By: Relevance
“…70 In another study, 430 subjects considered well controlled on FP/ salmeterol 250 mg/50 mg twice-daily were switched to once-daily fluticasone furoate (FF) 100 mg/vilanterol 25 mg for 8 weeks, and those who maintained control (n ¼ 371) were then randomized to monotherapy with FF 100 mg once daily, FP 100 mg twice daily, or FP 250 mg twice daily for 12 weeks. 71 No significant betweentreatment differences were determined for the time to withdrawal because of poorly controlled asthma requiring step-up therapy or the proportion of patients with well-controlled asthma at the end of treatment (co-primary variables), although again, lung function slightly declined across all 3 ICS monotherapies compared with the combination. 71 In contrast, both lung function and asthma control remained stable for 57 patients whose conditions were considered well controlled on either budesonide 320 mg/formoterol 9 mg twice daily or FP 250 mg/salmeterol 50 mg twice daily who were stepped down to ICS monotherapy with ciclesonide 320 mg once daily for 12 weeks.…”
Section: Stepping Down From Step 4 Therapymentioning
confidence: 93%
See 1 more Smart Citation
“…70 In another study, 430 subjects considered well controlled on FP/ salmeterol 250 mg/50 mg twice-daily were switched to once-daily fluticasone furoate (FF) 100 mg/vilanterol 25 mg for 8 weeks, and those who maintained control (n ¼ 371) were then randomized to monotherapy with FF 100 mg once daily, FP 100 mg twice daily, or FP 250 mg twice daily for 12 weeks. 71 No significant betweentreatment differences were determined for the time to withdrawal because of poorly controlled asthma requiring step-up therapy or the proportion of patients with well-controlled asthma at the end of treatment (co-primary variables), although again, lung function slightly declined across all 3 ICS monotherapies compared with the combination. 71 In contrast, both lung function and asthma control remained stable for 57 patients whose conditions were considered well controlled on either budesonide 320 mg/formoterol 9 mg twice daily or FP 250 mg/salmeterol 50 mg twice daily who were stepped down to ICS monotherapy with ciclesonide 320 mg once daily for 12 weeks.…”
Section: Stepping Down From Step 4 Therapymentioning
confidence: 93%
“…71 No significant betweentreatment differences were determined for the time to withdrawal because of poorly controlled asthma requiring step-up therapy or the proportion of patients with well-controlled asthma at the end of treatment (co-primary variables), although again, lung function slightly declined across all 3 ICS monotherapies compared with the combination. 71 In contrast, both lung function and asthma control remained stable for 57 patients whose conditions were considered well controlled on either budesonide 320 mg/formoterol 9 mg twice daily or FP 250 mg/salmeterol 50 mg twice daily who were stepped down to ICS monotherapy with ciclesonide 320 mg once daily for 12 weeks. 72 Some variability in lung function was reported, however, for 44 patients who were stepped down to budesonide 200 mg twice-daily, but whether this reflected the specific steroid or better adherence to once-daily treatment is unclear.…”
Section: Stepping Down From Step 4 Therapymentioning
confidence: 93%
“…Despite its clinical utility, a need remains to assess the link between ACT score and asthma treatment benefits and outcomes, and its suitability as an endpoint in clinical trials. Previous studies have used the ACT as a measure of response to treatment [5,6], including a recent Phase III study that was not published in time to be included in this review [7]. The aim of the current study was to assess the extent to which ACT score is correlated, or associated, with other important clinical, patient-reported, and economic asthma outcomes.…”
Section: Introductionmentioning
confidence: 99%
“…Taken together, the results of the current study and the previous study suggest that FF/VI is as effective as FP/SAL for both gaining and maintaining asthma control in a double-blind, randomized clinical trial setting. These results are further supported by the first period of a study conducted in Japanese patients, which demonstrated that patients maintained control when they stepped across from FP/SAL to FF/VI (19). In a recent study set in everyday clinical practice, FF/VI was shown to provide significant improvements in asthma control compared with usual care (ICS [± LABA]) (24).…”
Section: Discussionmentioning
confidence: 80%
“…Few studies have evaluated whether asthma control can be maintained when patients are stepped across from one ICS/LABA to another (18,19); therefore, this Phase IIIa study was conducted to evaluate whether FF/VI 100/25 µg OD was non-inferior to FP/SAL 250/50 µg BID in adult and adolescent patients with persistent asthma already well controlled on BID ICS/LABA. The study examined lung function and tolerability, as well as patientreported symptoms and quality of life.…”
Section: Introductionmentioning
confidence: 99%